PENGARUH PEMBERIAN REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN (STUDI PADA PDAM TIRTA TAMAN SARI KOTA MADIUN) - ALVIN DWI SATRIA ; Prof. Dr. Achmad Sudiro, SE, ME
This study aims to determine the effect of reward and punishment on employee_x000D_ performance of PDAM Tirta Taman Sari in the City of Madiun. The population used in_x000D_ this study was 148 employees of PDAM Tirta Taman Sari, City of Madiun. This study_x000D_ used the explanatory research method with a quantitative approach because the_x000D_ background of the initial research objective is to explain the influence of the variables to_x000D_ be studied and to explain the dominant influence between reward and punishment_x000D_ variables on employee performance, then to test the hypotheses that have been formulated_x000D_ previously. Data analysis was carried out using classical assumptions tests and hypothesis_x000D_ testing used multiple linear regression analysis, which was processed using a computer_x000D_ with SPSS 21.0 for Windows. The results obtained from this study were those employee_x000D_ reward variables (X1) and employee punishment variables (X2) have a significant effect_x000D_ on employee performance variables (Y), and employee reward variables (X1) are the_x000D_ most dominant variables affecting employee performance variables (Y). The magnitude_x000D_ (R2) of the three independent variables on the employee performance of PDAM Tirta_x000D_ Taman Sari in the City of Madiun was 54.1%, while the remaining 46.9% was influenced_x000D_ by other variables not examined in this study. _x000D_ _x000D_ Keywords: reward, punishment, employee performance